SPAG: A NEW MEASURE OF SPATIAL AGGLOMERATION. THEORETICAL BACKGROUND AND EMPIRICAL EXAMPLES - Kossowski, Tomasz; Hauke, Jan (Quaestiones Geographicae, 2018)
Kopczewska (2017) proposed a new empirical measure of spatial agglomeration (SPAG) of economic activity based on geolocations of firms. The aim of the paper is to introduce theoretical backgrounds of SPAG. The measure is a product of two random variables with beta and gamma distributions. The moments of the product are described and estimated for Poland with spatial centroids of LAU2 treated as geolocations of firms for empirical distribution as well as for the set of firms located in a regular region. Another approach to SPAG properties has its origin in a geometric probability concept. We present the research results on geometric probability, applied to SPAG, as distance probability distributions for a regular region.